CNSC-16. BIDIRECTIONAL SIGNALING BETWEEN GLIOBLASTOMA AND NEURAL PROGENITORS EXPLORED WITH CELL-SPECIFIC PROTEOMICS RESULTS IN INCREASED TUMOR MALIGNANCY AND ALTERED NEUROGENESIS IN THE SUBVENTRICULAR ZONE. (14th November 2022) - Norton, Emily; Whaley, Lauren; Jones, Vanessa; Brooks, Mieu; Zarco, Natanael; Russo, Marissa; Schiapparelli, Paula; Sanchez, Guadalupe; Ramos-Fresnedo, Andres; Rossoll, Wilfried; Chaichana, Kaisorn; Anastasiadis, Panos; et al.
Abstract: Glioblastoma (GBM) is the most common and aggressive primary neoplasm of the central nervous system. The location of GBM contributes significantly to patient outcomes, where tumors contacting the lateral ventricles (LVs) have increased expression of stem cell genes, increased incidence of distal recurrence, and decreased overall survival. While the reasons for these findings are not fully understood, we hypothesize they arise due to interactions with the subventricular zone (SVZ), the largest neurogenic niche in mammals. We examined bidirectional signals between GBM cells and neural progenitor cells (NPCs) in vitro and in vivo using a combination of patient-derived intraoperative samples, preclinical animal models, and the methionine tRNA synthetase L274G (MetRS*) nascent proteomic labeling system, which allows for cell-specific proteomics analysis from complex in vivo systems. In co-culture with NPCs, GBM cells increase their viability, proliferation, migration, and expression of malignancy-promoting proteins, including migratory proteins such as TAGLN, PALLD, and STAT1. In vivo, tumor proximity to the SVZ results in increased proliferation, increased expression of stemness markers, decreased survival, and altered tumor-specific proteome. We then examined the reciprocal effect of GBM cells on NPC biology. In vitro and in vivo, GBM cells decreased NPC proliferation and induced decreased neuronal maturation of NPCs. To determine NPC proteomic changes in vivo, we created a transgenic mouse line Nestin-CreERT2; STOPflox R26-MetRS L274G, where upon tamoxifen administration Nestin+ NPCs express GFP and MetRS*. Our results indicate that LV-proximal GBM induces decreased expression of neuronal maturation proteins such as Eml1, VGLUT1, and EAAT2, and an increase in pro-migratory factors such as Lamc1 in NPCs. In conclusion, there are bidirectional proteomic interactions between GBM cells and NPCs that contributes to altered neurogenesis and increased tumor malignancy of LV-proximal GBM. The signaling factors identified in our studies will result in identification of novel therapeutic targets for GBM.